Cultural Semiotics and Visual Mythmaking: The Role of Javanese Symbols in Modern Media Narratives - Ilham, Yanuar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study explores the semiotic representation of Javanese myth in the Marjan 3-Episode advertisement series, which centers on the figure of Dewi Sri, the Javanese goddess of rice and fertility. Using Roland Barthes’ theory of semiotics, the research analyzes selected scenes to uncover how visual signs operate on denotative, connotative, and mythological levels. The findings reveal that Dewi Sri is represented not only through traditional symbols such as rice fields, green costumes, and natural settings but also recontextualized within a modern cinematic advertisement format. This reflects a fusion between cultural heritage and contemporary marketing strategies. The advertisement transforms myth into a media narrative, presenting it as both spiritual and commercial symbolism during the Ramadan season. The study concludes that myth can still function ideologically in modern media, shaping consumer perception through layered meanings. This research contributes to the broader discussion on cultural identity in advertising and the role of semiotics in interpreting localized narratives in digital media.